The Bessel-Struve intertwining operator on ℂ and mean-periodic functions - A. Gasmi; M. Sifi (International Journal of Mathematics and Mathematical Sciences)
We give a description of all transmutation operators from the Bessel-Struve operator to the second-derivative operator. Next we define and characterize the mean-periodic functions on the space ℋ of entire functions and we characterize the continuous linear mappings from ℋ into itself which commute with Bessel-Struve operator.